Forging Connections in Early Mathematics Teaching and Learning (Early Mathematics Learning and Development,, 2018)
This edited book promotes thinking, dialogue, research and theorisation on multiple ways of making connections in mathematics teaching and learning in early childhood education. The book addresses some key challenges in research, policy and practice in early childhood mathematics education. It examines diverse ways for learning experiences to connect young children to mathematics, and the importance of forging connections between mathematics and young children's lives as key elements in their engagement with mathematics. Each chapter provides research or theoretical provocations and pedagogical implications for connecting children's lived experiences and ways of learning in mathematics teaching. The chapters are drawn from a range of international authors who raise important ideas within the overall context of current research and consider the theoretical and practical implications of their research. As such, the book advances current thinking on mathematics teaching and learning for children in the early years from birth to eight years with an emphasis on children aged birth to 5 years. It considers the purpose and value in connecting mathematics teaching and learning to children's lives, and provides provocations for both educators and researchers on the many under-researched and under-represented aspects of early years mathematics teaching and learning.